Interpretive quantification : methodological explorations for critical and constructivist IR - Barkin, J. Samuel, 1965-; Sjoberg, Laura, 1979- (University of Michigan Press, 2017)
"Countering the growing divide between positivists who embrace quantitative, numerical approaches and post-positivist scholars who favor qualitative, interpretive approaches, J. Samuel Barkin and Laura Sjoberg argue that both methods are more widely adaptable than is commonly assumed by either camp. In Interpretive Quantification, ten highly regarded scholars in the field of International Relations apply quantitative methods and formal models to specific constructivist and critical research questions. In this way, each chapter serves not only as evidence that methods can productively be applied across paradigms, but also as a guide as to how this may be done. In sum, the contributors make a compelling case that when researchers cordon off particular methods for merely ideological reasons, they circumscribe their own paradigms and hinder their own research agenda"--